Christian theology - Erickson, Millard J. (Grand Rapids, MI. Baker Books., 1999)
A comprehensive introduction to Protestant systematic theology, which covers the nature of God, God's plan and work, knowing and studying God, the doctrine of humanity, sin, the person and work of Christ, the Holy Spirit, salvation, the church, and eschatology.
Part 1. Studying God -- Part 2. Knowing God -- Part 3. What God is like -- Part 4. What God does -- Part 5. Humanity -- Part 6. Sin -- Part 7. The person of Christ -- Part 8. The work of Christ -- Part 9. The Holy Spirit -- Part 10. Salvation -- Part 11. The Church -- Part 12. The Last Things.
Includes bibliographical references and index.
Keywords: Theology, Doctrinal